Compte rendu de la passion. À propos de la lecture religieuse de Phèdre de Racine - Tomczak, Patrycja (Studia Romanica Posnaniensia, 2018)
The classicist, Christianized iteration of the myth of Phaedra demonstrates the particular nature of the tensions between Christian metaphysics and social morality. Based on the Pascal’s paradox of the righteous sinner. Racines Phèdre not only represents a certain historical, Jansenist system of values, but also makes it possible to see anew the aporias that have characterized Christian ethics until the present day: its deep anti-politics, the problematic relationship between erotic love, “mercy” and righteousness, the ambivalence of the virtue of temperance, or the connection between metaphysical purity and impersonal order.